Strategi Pengembangan Agrowisata Café Attaya di Desa Paslaten Kecamatan Kakas Kabupaten Minahasa Provinsi Sulawesi Utara - Manihuruk, Ira Dita Stevani; Kapantow, Gene Henfried Meyer; Baroleh, Jenny (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2023)
Tourism activities are not only an alternative for recreational activities, but these activities can increase income, if managed properly. For this reason, the right strategy is needed so that a business can develop properly. One of the businesses that is developing and utilizing agricultural areas is Cafe Attaya. This study aims to determine the development strategy for Cafe Attaya Agrotourism in Paslaten Village, Kakas District, Minahasa Regency, North Sulawesi Province. The sampling method in this study was taken using a combination of purposive sampling and accidental sampling techniques. Data was collected through interviews, observation, questionnaires, and literature studies. In analyzing the data using the SWOT analysis method. The results of the study show that Cafe Attaya's business position is in quadrant I (1.63; 0.87), which supports an aggressive strategy (growth). The strategy that Cafe Attaya can use is the SO strategy, including adding new photo objects to attract visitors, holding certain events or discounting prices on weekends.